Understanding the factors and consequences of student belonging in higher education: a critical literature review - David Gilani; Liz Thomas (Journal of Learning Development in Higher Education)
Student belonging is becoming an increasingly prominent concept in how universities pursue policies and practices to ensure student success. Through this increased prevalence, there has been a substantial increase in research output on this topic in recent years. This critical literature review aims to provide a comprehensive and accessible synthesis of research around the factors that affect student belonging and how it links to student success. Utilising a systematised search and appraisal method, 118 studies were included and reviewed. The existing literature has robustly shown the connections between belonging and many different aspects of student success – including student engagement levels, wellbeing, and retention. Critical analysis of the studies shows that the factors affecting student belonging are also multiple, although only some – such as experiential pedagogies and personalised support from staff – have been replicated in studies across multiple contexts and with experimental research methods. Importantly, there are also factors which negatively impact students’ sense of belonging – such as experiences of being stereotyped by staff. Utilising these findings around factors that influence student belonging, this article provides a set of recommendations for practitioners and identified gaps for future research on student belonging. Overall, this article contributes to understandings of how to impact students’ sense of belonging and how this links to student success.